2015
DOI: 10.1890/es15-00024.1
|View full text |Cite
|
Sign up to set email alerts
|

Colder rotifers grow larger but only in oxygenated waters

Abstract: Citation: Czarnoleski, M., J. Ejsmont-Karabin, M. J. Angilletta, Jr., and J. Kozlowski. 2015. Colder rotifers grow larger but only in oxygenated waters. Ecosphere 6(9):164. http://dx.doi.org/10.1890/ES15-00024.1Abstract. Why do colder ectotherms grow more slowly but mature at a larger size? Some researchers have argued that oxygen supply and demand play a crucial role in these processes, but many studies conflated the effects of oxygen and temperature. We studied the body sizes of rotifers (Keratella cochleari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…This is consistent with the results of earlier studies of inter-specific differences in Hb concentrations in Daphnia (Heisey & Porter, 1977;Sell, 1998), which indicated that larger-bodied species have higher basal levels of Hb, and synthesise more Hb in hypoxic conditions. Although each of the two properties induces energetic costs, they could be treated as adaptations to both greater vulnerability to hypoxia, since diffusion distances are increased in a larger body (Czarnoleski et al, 2015;Seidl et al, 2005), and greater vulnerability to fish predation, since larger-bodied Daphnia are prone to dwell more deeply in the oxygen-deficient meta-and hypolimnetic water layers to avoid size-selective predation by planktivorous fish in the euphotic layers (Hansson & Hylander, 2009;Leibold & Tessier, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results of earlier studies of inter-specific differences in Hb concentrations in Daphnia (Heisey & Porter, 1977;Sell, 1998), which indicated that larger-bodied species have higher basal levels of Hb, and synthesise more Hb in hypoxic conditions. Although each of the two properties induces energetic costs, they could be treated as adaptations to both greater vulnerability to hypoxia, since diffusion distances are increased in a larger body (Czarnoleski et al, 2015;Seidl et al, 2005), and greater vulnerability to fish predation, since larger-bodied Daphnia are prone to dwell more deeply in the oxygen-deficient meta-and hypolimnetic water layers to avoid size-selective predation by planktivorous fish in the euphotic layers (Hansson & Hylander, 2009;Leibold & Tessier, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia has been shown to reduce juvenile growth rate (Seidl et al, 2005), adult body size, and egg/neonate size (Hanazato & Dodson, 1995;Kobayashi & Hoshi, 1984;Lyu et al, 2013). Smaller adult body size in hypoxia could simply be attributed to slower juvenile growth, but it could also be treated as an adaptive response, since in a smaller body, diffusion distances are reduced, which contributes to an improved tolerance of hypoxia (Czarnoleski, Ejsmont-Karabin, Angilletta, & Kozłowski, 2015;Maszczyk & Brzeziński, 2018;Seidl et al, 2005). Moreover, due to smaller cell size, diffusion within tissues would be expedited (Woods, 1999), because oxygen more efficiently diffuses through a cell membrane than through the cytoplasm (Czarnoleski et al, 2015;Maszczyk & Brzeziński, 2018;Subczynski, Hyde, & Kusumi, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Note that some panels have different units of x and y axes [Colour figure can be viewed at wileyonlinelibrary.com] Kolding, Haug, & Stefansson, 2008). Similarly, the amphipod Asellus aquaticus raised at warmer temperatures grew to smaller adult sizes only when oxygen was limited (Hoefnagel & Verberk, 2015), and rotifers in low-oxygen lakes reached smaller body sizes than those in similar temperature but well-oxygenated waters (Czarnoleski, Ejsmont-Karabin, Angilletta, & Kozlowski, 2015). In contrast, other studies show that oviparous fish can increase their mass-specific oxygen consumption by nearly 30% compared to post-spawning fish (Karamushko & Christiansen, 2002), suggesting that changes in oxygen supply are regulated by the internal demands rather than supply.…”
Section: Are Aquati C Org Anis Ms Limited By Their C Apacit Y To Upmentioning
confidence: 99%
“…This mechanism was linked to the body size adjustment to temperature by Atkinson et al (2006). The hypothesis on the oxygen-driven size-to-temperature response has been positively verified both indirectly (Berner et al, 2007; Harrison et al, 2010; Rollinson and Rowe, 2018a; Rollinson and Rowe, 2018b; Santilli and Rollinson, 2018; Verberk and Atkinson, 2013) and directly (Czarnoleski et al, 2015; Frazier et al, 2001; Hoefnagel and Verberk, 2015). However, results relating this pattern directly to organismal fitness are scarce (Prokosch et al, 2019; Walczyńska et al, 2015a), while such a reference is the only way that enables reliable conclusions on the evolutionary meaning of TSR.…”
Section: Introductionmentioning
confidence: 81%